How Persistent Memory Will Change Software Systems - Badam, Anirudh (Computer, 2013)
Persistent memory promises to be byte addressable, fast, and nonvolatile as well as provide higher capacity and more efficient power consumption. System applications designers stand to gain much from these features, but some work is necessary to fully exploit them. The Web extra at http://youtu.be/nJBMJ2cLpcg is a an audio interview in which guest editor Simon S.Y. Shim interviews Anirudh Badam about persistent memory and its impact on future software systems.